Rate of resource utilization and cardiovascular outcomes in patients with low-risk chest pain at CCUs of hospitals affiliated with Shahid Beheshti University of Medical Sciences & Health Services - Shiri, H; Salarpour, Z; Ashketorab, T; Alavi Majd, H; Saadat, H (Advances in Nursing & Midwifery, 2010)
Background and Aim Many patients referring to health centers because of chest pain do not require hospitalization at CCUs (Coronary Care Units). The aim of this study was to assess the rate of resource utilization and cardiovascular outcomes in patients with low risk chest pain admitted to CCUs of hospitals affiliated with Shahid Beheshti University of Medical Sciences and Health Services. Materials and methods In this descriptive study, all patients with chest pain admitted to CCUs of 6 hospitals were selected with purposive sampling method. Of 550 patients, 95 were considered low-risk using "Thrombolysis in Myocardial Infarction (TIMI)" scale and assessed in terms of hospital stay, costs and cardiovascular outcomes over 30 days after discharge. A questionnaire validated with content and face methods was used for data collection. The scale was made reliable with inter-rater method (r=0.8). Data were analyzed with SPSS 16. Findings Mean age of the subjects was 46.95 year and 66.3% of them were male. The lowest stay and bed occupancy rates were related to hospital 3 and the highest rates to hospital 1 and 2. Mean length of stay was 3.04 days. ANOVA showed no significant difference between length of stay and expenses in 6 hospitals. No cardiovascular complication was seen 1 month after discharge in 89.5% of patients with any report of death. Conclusion With respect to the high rate of bed occupancy by the subjects and wastage of material and human resources with no cardiac complications over 1 month following discharge, appropriate triage of patients in the emergency unit can prevent unnecessary hospitalization in the CCU. Keywords: Low-risk patients, Chest pain, Resource utilization. *Corresponding Author: Hossein Shiri, .Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences and Health Services, Tehran, Iran E-mail: Shiri.hossein@yahoo.com